Patient-reported outcomes from a phase 3 study of baricitinib versus placebo or adalimumab in rheumatoid arthritis: secondary analyses from the RA-BEAM study. Issue 11 (10th August 2017) - Keystone, Edward C; Taylor, Peter C; Tanaka, Yoshiya; Gaich, Carol; DeLozier, Amy M; Dudek, Anna; Zamora, Jorge Velasco; Cobos, Jose Arturo Covarrubias; Rooney, Terence; Bono, Stephanie de; Arora, Vipin; Linetzky, Bruno; et al.
Abstract : Background: To assess the effect of baricitinib on patient-reported outcomes (PROs) in patients with active rheumatoid arthritis and an inadequate response to methotrexate (MTX). Methods: In this double-blind phase 3 study, patients were randomised 3:3:2 to placebo (n=488), baricitinib 4 mg once daily (n=487), or adalimumab 40 mg biweekly (n=330) with background MTX. PROs included the SF-36, EuroQol 5-D (EQ-5D) index scores and visual analogue scale, Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F), Health Assessment Questionnaire-Disability Index (HAQ-DI), Patient's Global Assessment of Disease Activity (PtGA), patient's assessment of pain and Work Productivity and Activity Impairment Questionnaire-Rheumatoid Arthritis (WPAI-RA), and measures collected in electronic patient daily diaries: duration and severity of morning joint stiffness (MJS), Worst Ttiredness and Worst Joint Pain. The primary study endpoint was at week 12. Treatment comparisons were assessed with logistic regression for categorical measures or analysis of covariance for continuous variables. Results: Compared with placebo and adalimumab, baricitinib showed statistically significant improvements (p≤0.05) in HAQ-DI, PtGA, pain, FACIT-F, SF-36 physical component score, EQ-5D index scores and WPAI-RA daily activity at week 12. Improvements were maintained for measures assessed to week 52. Statistically significant improvement in patient diary measures (MJS duration and severity), worst tiredness and worst joint pain were observed for baricitinib versus placebo and adalimumab at week 12 (p≤0.05). Conclusions: Baricitinib provided significantly greater improvement in most PROs compared with placebo and adalimumab, including physical function MJS, pain, fatigue and quality of life. Improvement was maintained to the end of the study (week 52). Trial registration: NCT01710358.